DINAMIKA KOMUNIKASI POLITIK DI INDONESIA: SYSTEMATIC LITERATURE NETWORK ANALYSIS (SLNA) - Firmansyah, Yusac; Saputra, Dwi Fajar (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
This study explores the dynamics of political communication in Indonesia through a Systematic Literature Network Analysis (SLNA). The research aims to understand the development and patterns of political communication within Indonesian scholarly literature. SLNA combines the Systematic Literature Review (SLR) using the PRISMA protocol to analyze article content, and Bibliometric Analysis (BA) to examine keywords, publication years, journals, and thematic networks. The study covers literature indexed in the Scopus database from 2014 to 2023. Literature mapping was conducted to identify connections among key concepts, theories, and existing research findings. The results show a clear evolution in the focus of political communication studies in Indonesia, ranging from historical perspectives during the independence movement to contemporary issues such as political communication during the COVID-19 pandemic by the executive branch, legislative communication trends, and identity politics. The study identifies specific research trends and highlights thematic shifts over time. It suggests the need for further studies to explore underexamined areas and encourages deeper analysis of the impact of new media and digital technologies on political processes in Indonesia. Overall, this study contributes to a more comprehensive understanding of Indonesia's political communication landscape and serves as a foundation for future research in the field.